Somerstown Stories and the benefits of using a design charette for community engagement. (1st July 2018) - Andrews, Martin; Court, Sharon; Goodman, David
Abstract : Somerstown Stories was a local heritage project supported by the Heritage Lottery Fund, collaborating initially with Somers Park Primary School in Somerstown, within the City of Portsmouth. The aim of the project was to enable people to reconnect with their locality by exploring local history. In addition, the project explored the question: does knowing more about where you live change how you feel about living there? At the time of the project, the area of Somerstown was at the beginning of a process of phased redevelopment, so it was timely for local groups and organizations as a whole to look back at their history and the shaping of the area, in order to prepare to look forward and plan for the future. As part of the larger Somerstown Stories project, the University of Portsmouth School of Architecture was invited to coordinate a design charette for Year 9 students from the local Charter Academy School. This paper explores the nature of the charette, and its value in engaging different stakeholders. The paper is written using commentaries, conclusions and reflections from the key people involved with this project, including Canon Nick Ralph from the Diocese of Portsmouth; Sharon Court, Creative Practitioner and Project Manager for the Somerstown Stories project; Martin Andrews, Architect and Principal Lecturer at the University of Portsmouth School of Architecture; and Andrew Joyce, a University of Portsmouth student at the time of the design charette and now a registered architect working at ArchitecturePLB in Winchester.